The implementation of prototype online information system for Seriab Secondary School Intranet - Mat, Rodzil; Azzali, Fazli; Md Saman, Azmi (2006)
An online system is any electronic interactive system that delivers information to the users via telephone lines to personal computers or via cables to terminals. So, online system is a great method of promoting flexible and fast access to a large data directly to the users without boundary. This project aims to develop the prototype online information system or SMK Seriab Portal to manage school activities better than the manual system. With this system teacher can download teaching courseware and syllabus; use online application and school calendar. Besides that, this project also aims to get teachers opinion on user’s satisfaction with portal system. The researcher find that gender, age and experience affect the user’s satisfaction. Overall, teachers are satisfied with content, accuracy, format, ease of use and timeliness of the portal.This finding will contribute to other researches as a guideline to develop related online information system.